Liquid Smoke-Based Pest and Disease Control for the Sekar Wangi Farmer Group in Padang Cermin Village, Selesai District, Langkat Regency - Kerista Tarigan; Rikson Asman Fertiles Siburian; Tua Raja Simbolon; Leo Ferdinan Hermando Hutabarat; Dewi Jernita Hulu; Natalia Lawolo; Jois Domini; Ramona Sefaca Situmorang (Talenta Publisher, 2026)
The excessive use of synthetic pesticides remains one of the major challenges in developing environmentally friendly agriculture. This community service program aimed to improve the knowledge and skills of members of the Sekar Wangi Farmer Group in producing and applying liquid smoke as a botanical pesticide. The activity was conducted in Padang Cermin Village, Selesai District, Langkat Regency, involving 20 active farmer group members. The methods included counseling, hands-on training on liquid smoke production through coconut shell pyrolysis, field demonstrations, mentoring, monitoring, and evaluation using pre-test and post-test instruments. The results showed a significant increase in participants’ understanding and practical skills. The average level of knowledge increased from 58% before the training to 89% after the activity. Participants were able to independently produce liquid smoke and apply it as an alternative pest and disease control agent. The program also resulted in a simple standard operating procedure (SOP) for liquid smoke production and application. The activity contributed to reducing dependence on synthetic pesticides while encouraging the utilization of local biomass waste and sustainable agricultural practices.